Oral collagen supplements intake on improving skin structure and function - Żyga, Justyna (Journal of Education, Health and Sport, 2022)
Introduction: Young and healthy skin is a beauty standard that generates the necessity of acceptance. Collagen supplements have recently grown in popularity and become a trendy product advertised as a remedy for various skin problems. As it turns out, numerous scientific studies have shown the benefits of hydrolyzed collagen supplementation in improving the signs of skin ageing. There are various animal sources of collagen, but marine fish collagen has the best safety profile, biocompatibility and bioavailability and remains the most frequent product used in scientific trials. Among newest randomised-control trials five were researched for this study to evaluate the efficacy of collagen supplementation and its influence of skin appearance with both objective and subjective assessment. State of knowledge: hydrolysed collagen supplementation demonstrated a significant reduction in wrinkles, improvement in skin texture, firmness and appearance. Moreover, studies show significant enhancement of the water content in the stratum corneum and epidermis. Reduction of transepidermal water loss and increased level of natural moisturising factor was observed. Conclusions: hydrolysed collagen supplements can delay and improve the signs of skin ageing by decreasing facial wrinkles and improving skin hydration and elasticity. Supplement intake is effective and safe - analysed studies have not reported any major adverse effects. Since reviewed trials lasted for no longer than 12 weeks, further studies are needed to evaluate the long-term use of hydrolysed collagen peptides.